Predictive control in matrix converters. Part I, Principles, topologies and applications - Rivera, Marco; Wheeler, Patrick; Olloqui, A. (2016)
This paper presents an overview of the predictive control principles applied to matrix converters and also the different topologies where this control technique is applied. It will be shown that the predictive strategy is a promising alternative to control matrix converters due to its simplicity and flexibility to include additional aspects in the control being suitable for different industrial applications.